ANALISIS STRATEGI PEMASARAN PADA BISNIS JASA TITIP BERDASARKAN PRINSIP-PRINSIP ETIKA BISNIS ISLAM (STUDI KASUS PADA INSTAGRAM @TWINSCOLL_) - Nor Alfi Laili; Dony Burhan Noor Hasan (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2023)
Online buying and selling has now spread worldwide, with trading systems and types of products being highly diversified. Consequently, proxy shopping services have emerged to facilitate the shopping process for the public. @twinscoll_ is one of the deposit service providers that has been running its business for quite some time. However, there are several reasons that make this proxy shopping business less effective. This research aims to identify and analyze the marketing strategies employed by the deposit service provider @twinscoll_ based on the principles of Islamic business ethics.The research methodology utilized in this study is qualitative, employing interview techniques with online purchasing service providers. Data sources include books, journals, and other references related to this research. This research is conducted due to the identification of some principles that do not align with Islamic business ethics, necessitating a shift in the business model based on Islamic principles. Therefore, this study explores new strategies implemented by the proxy shopping service in introducing or marketing its business without compromising Islamic principles.